Prevalence of thyroid disorders in type 2 diabetic patients - A 1-year cross-sectional study - Rikita Ramesh Mudhol; Shivakumar Veeranna Turamari; Rekha Ramesh Mudhol; B Srinivas (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Diabetes is one of the commonest health problem and has become a major health challenge worldwide. There is evidence from the literature suggesting that the intricate bond between Thyroid disorder and diabetes mellitus deceivingly contributes to micro and macro-vascular complications. OBJECTIVE: This study is being undertaken to determine an association between prevalence of thyroid disorders in Type 2 diabetic patients. MATERIAL AND METHODS: A hospital based prospective cross sectional study was carried out in the department of Medicine, at a tertiary care hospital in Belgaum. The study included 100 Type 2 diabetic patients who were interviewed for demographic details, duration of diabetes and history of other comorbid conditions. The patients were subjected to clinical examination and were investigated for fasting blood sugars, post prandial blood sugars, glycosylated haemoglobin (HbA1C), free triiodothyronine (T3), free thyroxine (T4) and thyroid-stimulating hormone (TSH). Data was analysed using SPSS statistical software version 20.0. RESULTS: The prevalence of thyroid disorder in type 2 diabetic patients was 35%. Of them 16% had subclinical hypothyroidism. The males outnumbered the females in the study and 22% of the males had thyroid disorder (P = 0.8390).Subjects in the age group of 61 to 70 years, prevalence was higher as compared to other groups (P = 0.0569).There was an increased risk of thyroid dysfunction in long standing type 2 diabetics (P = 0.0240).The prevalence was higher in patients with poor glycemic control, though the findings were not statistically significant (P = 0.1021). CONCLUSION: Thyroid Dysfunction is widely prevalent in patients with type 2 diabetes in our study. Hence it is prudent to screen routinely for Thyroid dysfunction in type 2 Diabetic patients, which will help in improving the quality of life and reduce the mortality rate.